Growth and Yield Performance of Tidal Local Aman Rice as Influenced by USG Application at Non Tidal Condition (Bangladesh Agronomy Journal, 2015)
An experiment was carried out at research field of Bangladesh Rice Research Institute, Gazipur to evaluate the performance of tidal local aman rice as influenced by urea super granule (USG) at non-tidal condition. Four tidal local aman varieties such as Sadamota, Razashail, Kutiagoni and Kalagura were used as planting materials. Nitrogen was applied as USG (1.8g) at 10 days after transplanting (DAT), 25 DAT, before panicle initiation (BPI) stage (date of PI stage of these 4 varieties were identified from previous experience) and no nitrogen (control). The experiment was laid out in a split-plot design where varieties in main plot and USG in sub-plot with three replications. Varietals response was significant on plant height, effective tillers hill-1, grains panicle-1 and grain yield. All the yield and yield components were influenced significantly by the time of USG application. Higher dry matter was produced by all the varieties when USG was applied at early growth stage (10 to 25 DAT) but crop lodges at milking stage due to more vegetative growth resulting increases sterility, decreases grain fertility and yield. On the other hand, when USG was applied at BPI stage grain fertility and yield were increased. The highest grain yield (3.51 t ha-1) was recorded from Kalagura when USG applied before panicle initiation stage. So, application of USG at BPI stage in local aman rice in non-tidal condition increased yield resulting higher gross and net return in all varieties.Bangladesh Agron. J. 2015, 18(1): 71-80